Spatially coupled channel coding design and analysis - Laouar Oulfa (University Of Eloued جامعة الوادي, 2020)
The growing need for cheaper communication and storage systems, faster and more reliable has forced many researchers to look for ways to reach the ultimate limits of reliable transmission and storage of information. Since the discovery of turbo turbo-codes and the subsequent rediscovery of LDPC codes a few years lat er, the field of channel coding has undergone several major advances. Until then, code designers were generally satisfied with the performance within a few decibels of the Shannon boundary, whereas new coding techniques now allow performance at a decibel f raction with modest coding and decoding complexity. Due to these significant improvements, coding standards in applications as diverse as mobile wireless communication, satellit satellite television and communications in distant space are being updated to incorpora te new techniques. In this work, we will present the structure and construction of the new particularly interesting spatial spatial-coupled code classes, the LDPC codes, which promise excellent performance in a wide range of channel conditions. We will also analys e the decoding techniques recommended for this class. Since spatial coupling is equivalent to the introduction of memory into the coding process, We will try to implement both a s imple construction all by maintaining satisfactory decoding performance to me et the requirements of the current standards of communication systems.
Intervention Abstract
Keywords: Channel coding; Spatially coupled coding; LDPC codes codes; Shannon boundary boundary; Coding and decoding techniques techniques